We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
86
1
avatar

let f(x)= (x+4)/(x+6)

f^-1(-8) = ???

 Mar 3, 2019
 #1
avatar+103122 
+1

Remember that some x value led to -8

 

So.....we can solve this to find f-1(-8)

 

(x + 4) / ( x + 6) = -8

 

x + 4 = -8 (x + 6)

 

x + 4 = -8x - 48

 

9x = - 52

 

x = -52/9    =  f-1(-8)

 

 

cool cool cool

 Mar 4, 2019

5 Online Users